HUBUNGAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG KOLOSTRUM DENGAN MOTIVASI PEMBERIAN KOLOSTRUM DI DESA SIDOREJO KECAMATAN SERAPIT KABUPATEN LANGKAT - Vitrilina Hutabarat; Stefani Anastasia Sitepu; Marlen Sadrina Sitepu; Ronalen Br Situmorang (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Babies given colostrum will facilitate breastfeeding success and can reduce 22 % of infant mortality below 28 days. This study uses analytic research with the method of cross sectional approach that aims to determine the relationship between the level of postpartum knowledge about colostrum with the motivation of giving colostrum in Sidorejo Village, Serapit District, Langkat Regency. The data collection technique in this study is total sampling by taking the total population of 30 postpartum mothers in March 2019. Variables in this study are dependent variables, namely motivation for giving colostrum and independent variables (independent), namely the level of postpartum knowledge about colostrum. The results in this study are that there is a significant relationship between the level of postpartum mothers knowledge about colostrum and the motivation for giving colostrum (p-value of 0.024)